Studi Bakteri Pendegradasi Fenol pada Lapisan Acrotelm dan Catotelm Di Hutan Rawa Gambut - Handayani, Wiji Pamungkas; Anshari, Gusti Zakaria; Indrawati, Urai Suci Yulies Vitri (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2023)
Peat soils are formed from woody materials which generally contain a lot of lignocellulosic organic compounds such as lignin which in the degradation process produces reactive carboxyl groups and phenolic compounds. Degradation of phenolic compounds can be carried out enzymatically by phenol- degrading bacteria. The purpose of this study was to compare the number of bacterial colonies degrading phenolic compounds in the acrotelic and catotelm layers in the upstream and downstream locations of the peat swamp forest in Permata Village, Terentang District, Kubu Raya Regency. Soil samples were taken in 2 plots (upstream and downstream from the canal blocking) at a distance of 500 meters using a peat drill. Each plot was then taken 3 drill points to form a triangular pattern with a distance of 30 meters with a peat depth level (Acrotelm) 0-10 cm, 10-20 cm and peat depth (Catotelm) 300-310 cm, 310-320 cm. Bacterial colonies were counted using the Total Plate Count method on Mineral Salt Medium and pure phenol selective media. Total phenolic compounds in peatlands were tested using 10% Folin-Ciocalteu solution and 2% Na2CO3. The number of bacterial colonies at locations upstream from the canal blocking in the acrotelmic layer is 0-10 cm deep (7,5x104 cfu/gr) and 10-20 cm deep (8,8x104 cfu/g), while bacteria in the catotelm layer are 300-310 cm deep (2,1x104 cfu/gr) and a depth of 310-320 cm (2,2x104 cfu/gr). The number of bacterial colonies downstream from the canal blocking in the acrotelm layer at a depth of 0-10 cm (2,3x104 cfu/gr) and at a depth of 10-20 cm (3,1x104 cfu/gr), while bacteria in the catotelm layer at a depth of 300-310 (1,7x104 cfu/g) and a depth of 310-320 cm (1,6x104 cfu/g).